2017
DOI: 10.1038/s41598-017-00895-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostic assays based on cpn60 UT sequences reveal the geographic distribution of subgroup 16SrXIII-(A/I)I phytoplasma in Mexico

Abstract: Geographically diverse samples from strawberry exhibiting symptoms of Strawberry Green Petal (SbGP), periwinkle plants with virescence, and blackberry, blueberry, and raspberry plants displaying yellowing and inedible fruits, were assayed for the presence of phytoplasma DNA. PCR targeting the 16S rRNA-encoding gene and chaperonin-60 (cpn60) showed that the plants were infected with phytoplasma subgroup16SrXIII-(A/I)I (SbGP/MPV). To examine the geographic distribution of this pathogen in Mexico, we designed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
(98 reference statements)
0
18
0
1
Order By: Relevance
“…The time to positive found by Castro et al 33 investigating a rapid diagnosis of Zika virus was found to be in the same 13-15 minute range as our work described here. An inverse relationship between time to positive and input copy number that was linear over several orders of magnitude was also demonstrated for a Strawberry Green Petal phytoplasma (16SrXIII) LAMP assay 15 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The time to positive found by Castro et al 33 investigating a rapid diagnosis of Zika virus was found to be in the same 13-15 minute range as our work described here. An inverse relationship between time to positive and input copy number that was linear over several orders of magnitude was also demonstrated for a Strawberry Green Petal phytoplasma (16SrXIII) LAMP assay 15 .…”
Section: Discussionmentioning
confidence: 68%
“…Results were analyzed using a 2x2 table and sensitivity and speci city along with 95% con dence intervals calculated as described 25 . Samples that were discordant (LAMP positive/nested PCR negative) were re-analyzed using BBSP-speci c real-time qPCR as described here (Table S1) as well as using nested PCR targeting the ribosomal protein (rp) operon 15 . For rp operon ampli cation, primers rpF1/rpR1 37 were used in the rst round, then the PCR product was diluted 1:30 and 2 µl used in a second round with primers rp(I)FIA/rp(I)RIA 38 .…”
Section: Validation Of the Lamp Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Inicialmente la identificación de fitoplasmas se realizó mediante técnicas como Western Blot, hidrólisis de ADN, separación mediante centrifugación, Cromatografía Líquida de Alta Resolución (HPLC, por las siglas en inglés de High Performance Liquid Chromatography), hibridación, entre otras (Kollar y Seemüller, 1989). Sin embargo, la inclusión de la técnica de PCR y de sus variantes han permitido complementar su diagnóstico, además de corroborar, cuantificar e incluso identificar nuevos fitoplasmas (Torres et al, 2005;Obura et al, 2011;Pérez-López et al, 2017).…”
Section: Técnicas De Identificaciónunclassified
“…Mollicutes (Phylum Firmicutes ) are a class of microorganisms that include phytoplasmas (‘ Candidatus Phytoplasma’) that are being increasingly recognized for their role in plant diseases such as sapodilla little leaf, yellow leaf roll disease of peach, strawberry green petal and sugarcane white leaf syndrome. These diseases affect a diverse array of economically and ecologically important plant hosts around the world (Vesterinen et al, 2013 ; Pérez-López et al, 2016 , 2017 ). Mollicutes are highly diverse and are made up of five orders, Acholeplasmatales, Anaeroplasmatales, Entoplasmatales, Haloplasmatales, and Mycoplasmatales.…”
mentioning
confidence: 99%